Retroperitoneal Mullerian Cyst of Renal Origin in a Cat - A Case report - M, Gokulakrishnan; Pradeep (Indian Journal of Veterinary Medicine, 2024)
Extreme rarely reported mullerian cysts of the retroperitoneum are considered to be a subtype of urogenital cysts. Retroperitoneal cysts can be categorized into lymphatic cysts, mesothelial cysts, enteric cysts and urogenital cysts based on embryological origin and histogenesis. The present case is an rare encounter and the successful management of the same is herewith discussed. A twelve months old intact female domestic short hair cat was presented with a history of progressive abdominal distension, anorexia, lethargy and oliguria. On abdominal palpation, an extensive globular mass was palpable in the cranial abdomen a survey radiography of the abdomen and thorax revealed a soft tissue contour at the cranial abdomen at the left renal position, thoracic radiography revealed absence of any abnormalities. Renal functional status was ascertained with intravenous pyelography which revealed unilateral cystic dysgenesis of left kidney and agenesis of left ureter. Hematobiochemical profiles and preoperative assessment were done to rule out general organ health. Following routine and special diagnostic procedures, an exploratory laparotomy confirmed the cystic renal distension that was excised through an unilateral nephrectomy and the cat was observed on periodic reviews to confirm any abnormalities if any which was absent and the animal had an uneventful recovery,.